1970
DOI: 10.3329/jbau.v7i1.4983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary levels of vitamin E on the ovarian development and breeding performances of <i>Clarias batrachus</i> (Linnaeus)

Abstract: To observe the effects of vitamin E on the ovarian development and breeding performances of Clarias batrachus an experiment was conducted in two phases. The first phase concentrated on studying the effects of vitamin E on ovarian development and the second phase on breeding performances. Eighty female C. batrachus broodfish were stocked in 8 cisterns (2.38 × 1.45m 2 each) divided into 4 treatments each having two replicates. Each of the cistern was stocked with 10 females. The fish were fed with feed having di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
(1 reference statement)
2
5
0
Order By: Relevance
“…Stated that nutrition in broodstock feed can affect gonadal development, fecundity, and embryo development [18]. This was in line with the results of the study where the addition of enriching ingredients in feed such as glutathione and vitamin E resulted in the highest GSI among other treatments.…”
Section: Discussionsupporting
confidence: 84%
“…Stated that nutrition in broodstock feed can affect gonadal development, fecundity, and embryo development [18]. This was in line with the results of the study where the addition of enriching ingredients in feed such as glutathione and vitamin E resulted in the highest GSI among other treatments.…”
Section: Discussionsupporting
confidence: 84%
“…Relevant studies have been carried out on a number of fish species such as ayu (Takeuchi et al, 1981), goldfish (Kashani et al, 2012), carp (Taati et al, 2010), Nile tilapia (Gammanpila et al, 2007), black sea trout (Serezli et al, 2010), guppy (Mehrad and Sudagar, 2010), and zebrafish (Mehrad et al, 2012), which suggested that dietary Ve can improve the reproduction of broodstocks and survival rate of larvae. In female fish, it has been widely observed that dietary Ve could improve diverse reproductive performance such as the number of spawners (Areechon et al, 2003), ovarian growth rate (Watanabe and Takashima, 1977;Gupta et al, 1987;Roy and Mollah, 2009), vitellogenesis (Kanazawa, 1985;Santiago and Gonzal, 2000), and egg quality (Izquierdo et al, 2001;Kashani et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The maximum GSI values for either male or female C. macrocephalus in the present study were elicited at 215-216.2 mg•kg -1 . In Clarias batrachus, the highest GSI was observed in the 100 mg•kg -1 group, followed by 200, 0, and 50 mg•kg -1 (Roy and Mollah, 2009). In goldfish Carassius auratus, 100 mg•kg -1 VE was reported suitable for stimulating the development of gonads and spawning (Sanchai-Sutjaritvongsanon, 1987).…”
Section: Discussionmentioning
confidence: 99%